Seismic phases of 25 April 2015 (Mw 7.8) Earthquake and 12 May 2015 (Mw 7.3) Earthquake Predicted by AK135 Model - A comparison (Journal of Nepal Physical Society, 2021)
A strong Mw 7.8 (depth = 8.2 km) earthquake initiated ~80 km northwest of the Kathmandu on 25 April of 2015 was followed by the Mw 7.3 (depth = 15 km) earthquake on 12 May. The seismic phases of these earthquakes were predicted at Kakani, Kathmandu seismic station (27.80°N and 85.28°E) using software model AK135 . The model predicts 21 arrivals for Gorkha earthquake with first p phase arriving at incident angle 82.65° in 11.516 seconds and final phase SKIKSSKIKS in 3270.791 seconds with incident angle 0.02°. Similarly, for the Dolakha earthquake 27 arrivals are predicted with the first arrival p phase at incident angle 74.35° in 14.504 seconds and final arrival SKIKSSKIKS phase at incident angle 0.03° in 3268.823 seconds. The 5 depth phases and 8 core phases predicted are similar for both the earthquakes while 8 and 12 mantle phases are predicted for Gorkha earthquake and Dolakha earthquake respectively. In addition, two crustal phases (Pn, Sn) were predicted only for Dolakha earthquake. The additional phases are critically refracted seismic phases indicating the existence of the Moho discontinuity between the crust and upper mantle. Their existence for Dolakha earthquake could be the indication of different geological provinces of the source region of the earthquakes, differing in age, crustal thickness, temperature, and tectonic stress. The ratio of P wave ad S wave velocity is found to be 1.67 for the regions. These seismic phases reflect their sensitivity to different layers of the earth and carry information about the geometrical and physical properties of discontinuities inside the earth.